Transcriptional regulation of tumour necrosis factor-related apoptosis-inducing ligand - Md. Azahri, Nor Saadah; Kavurma, Mary M. (Birkhauser Verlag Basel, 2013)
Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) has dual functions mediating both apoptosis and survival of cells. This review focusses on the current regulatory factors that control TRAIL transcription. Here, we also highlight the role of distinct transcription factors that co-operate and regulate TRAIL in different pathological states. A better understanding of the molecular signalling pathways of TRAIL-induced cell death and survival in disease may lead to more sophisticated technologies for novel therapeutic targets. © 2013 Springer Basel.